2013
DOI: 10.1177/1350508412473865
|View full text |Cite
|
Sign up to set email alerts
|

Being occupied: An embodied re-reading of organizational ‘wellness’

Abstract: ‘Organizational wellness’ has become a high profile issue for businesses. We argue that a ‘wellness movement’ has sprung up around a particular coalescence of economic, ideological and organizational interests. In this article we re-read the discourse of this ‘movement’ through the lens of ‘organized embodiment’. We argue that organizational wellness operates as a rhetorical device which masks contradictory power relations. It serves to hide differential occupational effects and opportunities for workers, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
87
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(89 citation statements)
references
References 41 publications
0
87
0
2
Order By: Relevance
“…Social theorists have advocated perspectives reflecting similar affective and embodied practices (Clough & Halley, 2007;Clough, 2008;Thrift, 2007), while cultural anthropologists have offered analogous views on sense perception processes (Brennan, 2004;McGrail, Davie-Kessler & Gruffin, 2015;Protevi, 2009). Closer to home, writers in organization studies have suggested the need for innovation and creativity in embodied and affective analysis (Dale & Burrell, 2014;Lennie, 2000;Riach &Warren, 2014). In other words, scholars from a number of fields have advocated approaches to ethnographic-related research that seek to We suggest therefore numerous innovative ways to conceptualise affect and embodiment in video-based organizational ethnography -modes of expression that move us beyond habitual realist, objectivist and Cartesian assumptions.…”
Section: Theorizing Subjectivelymentioning
confidence: 99%
See 1 more Smart Citation
“…Social theorists have advocated perspectives reflecting similar affective and embodied practices (Clough & Halley, 2007;Clough, 2008;Thrift, 2007), while cultural anthropologists have offered analogous views on sense perception processes (Brennan, 2004;McGrail, Davie-Kessler & Gruffin, 2015;Protevi, 2009). Closer to home, writers in organization studies have suggested the need for innovation and creativity in embodied and affective analysis (Dale & Burrell, 2014;Lennie, 2000;Riach &Warren, 2014). In other words, scholars from a number of fields have advocated approaches to ethnographic-related research that seek to We suggest therefore numerous innovative ways to conceptualise affect and embodiment in video-based organizational ethnography -modes of expression that move us beyond habitual realist, objectivist and Cartesian assumptions.…”
Section: Theorizing Subjectivelymentioning
confidence: 99%
“…In our current empirical work, for example, a 'body as narrative' view suggests that video-based research can vividly capture the many discursive struggles that managers and workers, relatives and residents, engage in to produce a discourse of the (primarily aged) body. Drawing on Foucault's (1979) notion of the semiotic body as a 'trace of culture', one possibility is to capture the espaliering of embodiment (Dale & Burrell, 2014) and how through such 'capturing' the subject gradually submits to the needs of the organization, or alternatively resists such colonising processes.…”
Section: Participatory Filmmaking and Research Opportunitiesmentioning
confidence: 99%
“…CW is a response to 'illness-related loss of productivity due to absence from work (absenteeism) and reduced performance while at work (presenteeism) ' (Mattke et al, 2013: xiii). Rather than demonstrating the social legitimacy of the firm, CW involves an 'intensification of the links between wellness and economic interest' (Dale and Burrell 2014: 3) thereby relegating social legitimacy to an ancillary position, clearly aligning the purpose of worker wellbeing with the economic objective of HRM.…”
Section: What Is Cw?mentioning
confidence: 99%
“…Through this lens, WHP is an extremely powerful expression of the hegemonic (consent) based model of management that inspires effort because workers feel that they ought to do more for a firm that contributes to societal health. Worker wellbeing perceived as a means of enhancing the economic performance of the firm (i.e., as CW), on the other hand, is more closely aligned with a domination model of management at the heart of which is surveillance of performance across a range of work and extra work metrics (see, for example, Hull and Pasquale 2017; Dale and Burrell 2014). The normative theory of wellbeing thus does not apply to CW.…”
Section: Why Not? Theorising Cwmentioning
confidence: 99%
“…Arguably, this is emblematic of a wider poor perception of mental illness in the UK and beyond, an illness that still struggles to be recognized and respected alongside other more outwardly visible, measurable, and treatable biological conditions (Mind 2013). Indeed, one of the challenges of understanding mental health generally is that 'health' and 'illness' are treated as such definitive and opposing labels (Dale and Burrell 2014;Jack and Brewis 2005).…”
Section: Taking Ostensive Actionmentioning
confidence: 99%